Laporan Kasus : Septo Optic Dysplasia (de Morsier Syndrome) - Sony Sutrisno (Jurnal Kedokteran Meditek, 2020)
Septo optic dysplasia (SOD) is a rare disease with 1 of 10,000 live births incidence. It consists of midline brain structure dysgenesis, optic nerve dysgenesis, and pituitary disfunction. We report an 11 year old female with strabismus and visual impairment. Eye examination showed that her visual acuity is 1/60 for right eye and 6/6 for left eye. Neither delay developmental nor neurological disorder was found. Brain CT showed hypoplasia of the right optic nerve sheath and the absence of septum pellucidum. The pituitary was observed to be within the normal limit. Radiology examination has an important role as one of diagnostic tools for SOD because of its superiority in evaluating brain structure and optic nerve.